2019
DOI: 10.1021/acsmacrolett.9b00750
|View full text |Cite
|
Sign up to set email alerts
|

Telechelics Based on Catalytic Alternating Ring-Opening Metathesis Polymerization

Abstract: We describe a protocol to synthesize alternating telechelic ROMP copolymers of 7-oxa-norbornene derivatives and cycloalkenes under catalytic conditions. These copolymers were synthesized using Grubbs' second-generation catalyst. The sterically less hindered backbone double bonds of the resulting alternating copolymers facilitate the chain transfer (secondary metathesis) reactions. In the presence of symmetrical chain transfer agents (CTA), alternating copolymers could be synthesized catalytically. This procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…It has been known that the addition of a difunctional chain transfer agent (CTA) in a ROMP reaction would result in the formation of telechelic polymers with controlled molecular weight and functionality . This method relied on backbiting or secondary metathesis reactions between CTA and polymers formed in order to reach a thermodynamically equilibrated state . In the last decades, plenty of functionalized polymers have been synthesized bearing various groups via chain‐transfer ROMP, such as acetoxy, hydroxyl, carboxyl, amino, ester groups, and so on.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…It has been known that the addition of a difunctional chain transfer agent (CTA) in a ROMP reaction would result in the formation of telechelic polymers with controlled molecular weight and functionality . This method relied on backbiting or secondary metathesis reactions between CTA and polymers formed in order to reach a thermodynamically equilibrated state . In the last decades, plenty of functionalized polymers have been synthesized bearing various groups via chain‐transfer ROMP, such as acetoxy, hydroxyl, carboxyl, amino, ester groups, and so on.…”
Section: Introductionsupporting
confidence: 58%
“…Due to the higher strain energy of NB (113.9 kJ/mol) than that of COE (31.1 kJ/mol), NB has more tendency to undergo the ROMP than COE with G2 catalyst, which resulted in the slightly higher molar fraction of NB incorporated in the copolymers determined by 1 H NMR spectroscopy than that in the feeding ratio, which was in accordance with the previous report . It has been reported that the chain‐transfer ROMP method relied on the secondary metathesis reactions between the chain transfer agent and polymers formed in the beginning in order to reach a thermodynamically equilibrated state . The difficulty of secondary metathesis mainly depended on the steric hindrance around the double bonds, thus polycyclooctene was more favorable to undergo secondary metathesis than polynorbornene with five‐membered rings around the double bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, 1-endo has a low reactivity it still undergoes homopolymerization. 59 The lower reactivity of bridgehead substituted oxanorbornene imide derivatives towards ROMP had been reported previously. 64 The presence of steric bulk at the bridgehead position makes the monomer less accessible for coordination to alkylidene catalysts and thus results in slower polymerization.…”
Section: Initiation Studiesmentioning
confidence: 54%
“…57,58 Recently, our group also reported AROMP with oxanorbornene imide (oxaNBE) derivatives even at elevated temperature using G2. 59 However, under similar conditions, the corresponding norbornene derivatives exhibiting comparable ring strain mainly yielded block copolymers. [60][61][62][63] To the best of our knowledge, a norbornene derivative that undergoes a strict single addition to a metathesis initiator has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%